THE MAIN DETERMINANTS OF THE TOOLS OF FINANCIAL PLANNING AS AN INDICATIVE SCHEME OF REDUCTION OF CRISIS SITUATIONS - S. Yunusova; A. Bodiako (Вестник университета)
Logical reflection of this article is based on definition of key positions of the finance director within financial planning of the company. Besides the differentiated exit methods from crisis situations of the company are considered. Reflection of strategy of the company through Issikava's chart is offered and also the budgeting tools quintessence is defined. The earlier the finance director, using preventive methods of anti-recessionary planning, diagnoses each crisis symptom, the enterprise will have great opportunities for neutralization of the broken balance.